Accounting Literacy and Financial Management Training to Optimize Productive Zakat for Mustahiq in Kutai Kartanegara (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The poor level of accounting literacy and financial management among mustahiqs receiving productive zakat under the supervision of the Amil Zakat Institution Dana Peduli Umat (LAZ DPU) in Kutai Kartanegara has resulted in inefficient use of zakat funding for microenterprise growth. This Community Service Program (PKM) aims to strengthen accounting literacy and financial management in Kutai Kartanegara, so that mustahiq can be more economically independent through productive zakat management. Through interactive training, on-site mentoring at business sites, and reinforcement of Sharia-based financial management concepts, the PKM Program uses a participatory, andragogy-based approach. 46 mustahiqs and students participated in events in Embalut and Pariaman Villages, Kutai Kartanegara, as part of the Merdeka Belajar Kampus Merdeka program. The evaluation findings show a significant improvement in participants' accounting literacy and financial management practices. The average pre-test score of 38 rose to 91 in the post-test (a 139% increase). In addition, 84.8%  participants have started to adopt digital accounting tools. The mustahiq are now able to separate business and household finances, prepare monthly budgets, and compile simple income statements. The PKM program has been successful in improving Mustahiq's ability to run their business more independently and accountably. According to the Mustahiq Naik Kelas Action Plan, every participant (100%) signed and turned in a written commitment to the East Kalimantan DPU LAZ. Long-term, it is anticipated that this initiative will promote the conversion of mustahiq into muzakki, maximize the use of profitable zakat contributions, and help meet the Sustainable Development Goals (SDGs) and reduce poverty at the local and regional level.